KEPRIBADIAN PEMIMPIN DALAM PERSPEKTIF ADAT MELAYU RIAU: KAJIAN NILAI DAN ETIKA KEPEMIMPINAN - Hermandra, Hermandra; Elmustian Elmustian; Dila Apri Kanisya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to examine the personality of leaders from the perspective of Riau Malay customs, with an emphasis on leadership values and ethics. Riau Malay customs contain noble principles that serve as guidelines for shaping the character of leaders who are integral, wise, and responsible. The method used is qualitative research with a literature study approach. The results of the study indicate that the personality of leaders in Riau Malay culture is characterized by values such as trustworthiness, fairness, wisdom, humility, as well as upholding deliberation (consensus). These values are relevant in the context of modern leadership as a foundation for creating harmonious and sustainable organizational governance.